The Allegiance of Women, A Historical Study of Social Implications and Dimensions - Ahmed, Muayad (Islamic Sciences Journal, 2023)
In our present time, the issue of women in Islamic societies has become one of the topics around which social issues are raised under the pretext that women in the view of the Islamic religion are restricted to freedom and deprived of will and do not enjoy the rights, There are calls for their liberation from the responsibility of their families, which is nothing but a pretext for establishing forbidden relationships, showing off, and going out without their mahrams under the pretext Equality with men. Therefore, the topic of our research entitled ((The allegiance of women, a historical study of social implications and dimensions)) which shows the reason for the limits set by Allah in the Islamic Sharia, by which men and women are prevented from doing some forbidden actions, which are the same actions that advocates of liberation call for women in our present time and consider them among the restrictions imposed on women. Women have positive dimensions for any society, as they deny some values and morals that offend women and scratch the modesty of society and make it a disintegrated society in terms of the sound norms and traditions that Allah wanted for the servants.